Integrated optimal design of control system of smart structures using genetic algorithms - Jin, Zhanli (2008)
The main objective of this study is to develop an integrated optimization system based on GAs for the optimal design of control system of smart structures, which includes the placement and size of piezoelectric patches, as well as the feedback control gains.